LEON, Anthony James Inventory of documents - LEON, Anthony James (ARCA, 2018)
Private papers of Tony Leon, MP for Democratic Party, Houghton 1989; Chairman of the Bill of Rights Commission 1990 – 1994; advisor to the Convention for a Deocratic South Africa (CODESA) and delegate to the multi-party negotiations that led to the end of apartheid and establishment of a multi-party democracy in 1994; at the 1994 general elections again elected to Parliament in the first democratic National Assembly, and leader of the Democratic Party; in 1999 he became Leader of the Opposition as the DP took 38 seats. After the 2004 general elections, the Democratic Alliance under Leon had a vote increased by 2.8%.
COVERAGE 1990-2009; 1120 Files; 11 Metres.
Keywords: LEON, Anthony JAmes; Inventories; Politicians; Democratic PArty; Democratic Alliance